2017
DOI: 10.1016/j.celrep.2017.10.099
|View full text |Cite
|
Sign up to set email alerts
|

CISD2 Haploinsufficiency Disrupts Calcium Homeostasis, Causes Nonalcoholic Fatty Liver Disease, and Promotes Hepatocellular Carcinoma

Abstract: CISD2 is located within the chromosome 4q region frequently deleted in hepatocellular carcinoma (HCC). Mice with Cisd2 heterozygous deficiency develop a phenotype similar to the clinical manifestation of nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH). Cisd2 haploinsufficiency causes a low incidence (20%) of spontaneous HCC and promotes HBV-associated and DEN-induced HCC; conversely, 2-fold overexpression of Cisd2 suppresses HCC in these models. Mechanistically, Cisd2 interacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 36 publications
2
46
0
Order By: Relevance
“…There are two Dosmit homologs in mammals: Cisd1 and Cisd2 51,52 . These two proteins show different subcellular localization patterns and may have distinct functions, since Cisd2 has a longer N-terminal domain and is located mainly in the ER 63 , while Cisd1 has a shorter N-terminal domain and is located mainly on mitochondria 51 ( Supplementary Fig. 16b).…”
Section: Discussionmentioning
confidence: 99%
“…There are two Dosmit homologs in mammals: Cisd1 and Cisd2 51,52 . These two proteins show different subcellular localization patterns and may have distinct functions, since Cisd2 has a longer N-terminal domain and is located mainly in the ER 63 , while Cisd1 has a shorter N-terminal domain and is located mainly on mitochondria 51 ( Supplementary Fig. 16b).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, UPR causes upregulation of the tribbles homolog 3 (TRB3), which inhibits signaling via the insulin receptor axis ( 133 , 134 ). In addition to insulin resistance, elegant studies using a genetic mouse model of impaired ER calcium reuptake by genetic ablation of the SERCA activator Cisd2 have implicated reduced ER calcium levels and resulting ER stress in the development and progression of NAFLD ( 135 ).…”
Section: Calcium Signaling In Chronic Liver Injurymentioning
confidence: 99%
“…Although both diagnostic and therapeutic strategies for HCC have improved over the past decades, the 5-year survival rate only is around 10%, and HCC continues to be a global health issue, especially in Asian countries [ 3 , 4 ]. Emerging evidence suggested that nonalcoholic fatty liver disease (NAFLD), a common disorder in obese people, is a significant risk factor for HCC [ 5 , 6 ]. Given the global prevalence of obesity, there is the looming threat of a rapidly rising occurrence of NAFLD-related HCC.…”
Section: Introductionmentioning
confidence: 99%